2000
DOI: 10.1074/jbc.275.1.177
|View full text |Cite
|
Sign up to set email alerts
|

N-Acylated Serinol Is a Novel Ceramide Mimic Inducing Apoptosis in Neuroblastoma Cells

Abstract: A novel structural analog of ceramide was synthesized by N-acylation of serinol (2-amino-1,3-propanediol) and studied for its effects on glycolipid biosynthesis and cell differentiation of neuroblastoma cells. Incubation with N-palmitoylated serinol (C16-serinol) increased the concentration of endogenous ceramide by 50 -80% and caused apoptosis in rapidly dividing low density cells but not in confluent cells. Cell death was not suppressed by simultaneous incubation with phorbol ester, known to antagonize ceram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
80
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 45 publications
(57 reference statements)
10
80
0
Order By: Relevance
“…The effect of several chemotherapeutic agents are linked to the induction of apoptosis and associated with an increase of cellular ceramide (Bieberich et al, 2000;Macchia et al, 2001). In the present study, we found that ceramide induced apoptotic cell death in U373MG cells, detected by decrease of mitochondrial membrane potential or phosphatidylserine exposure measured by Annexin V binding.…”
Section: Discussionsupporting
confidence: 50%
“…The effect of several chemotherapeutic agents are linked to the induction of apoptosis and associated with an increase of cellular ceramide (Bieberich et al, 2000;Macchia et al, 2001). In the present study, we found that ceramide induced apoptotic cell death in U373MG cells, detected by decrease of mitochondrial membrane potential or phosphatidylserine exposure measured by Annexin V binding.…”
Section: Discussionsupporting
confidence: 50%
“…Sustained elevation of ceramide was observed after treatment with our analogs: a finding also described with other ceramide mimics, including Nacylated-serinol, B13 and diene-ceramides. 8,9,14 Interestingly, the present study shows that ceramide accumulation occurs upstream of the mitochondrial events since, in contrast to execution of the cell death program, it was not suppressed by Bcl-xL overexpression. Several mechanisms could account for ceramide elevation : inhibition of SM and GlcCer synthases (present study), inhibition of ceramide degradation by cerami- Ceramide analogs trigger Jurkat cell death T Granot et al dase, 9 or ceramide-induced 'self-accumulation'.…”
Section: Ceramide Analogs Trigger Jurkat Cell Death T Granot Et Almentioning
confidence: 84%
“…25 N-acylated derivatives of serinol also caused apoptosis of neuroblastoma or breast cancer cells. 8,26 Further analogs exhibited cytotoxicity against cancer cells, including compounds containing a thiouracil ring, 27 benzene, 28 or 4,6-diene-ceramides. 14 In addition to the numerous effects reported on different cell culture models, several ceramide analogs proved to be effective in vivo, some of them having been administered as liposomes.…”
Section: Ceramide Analogs Trigger Jurkat Cell Death T Granot Et Almentioning
confidence: 99%
See 2 more Smart Citations